Physical property analysis of biodiesel from nyamplung and used cooking oil: density, viscosity, calorific value, and flash point - Wahyudi, Wahyudi; Nadjib, Muhammad; Faizi, Achmad (Jurnal Polimesin, 2024)
The increasing dem and for energy and the depletion of fossil fuel shas led to the exploration of alternative fuels like biodiesel, which require sref inement tomatch diesel oil properties. This study investigates the combination of nyamplung oil, a non-edible potential source, with waste cooking oil for biodiesel production, aiming to improve its physical properties. Through a method ological approachin volving degumming, esterification, and transesterification, biodiesel was produce dfrom these oils in 11 different blend compositions. The physical properties of these blends, including density, viscosity, flashpoint, and calorific value, were rigorously tested. Results indicate that incorporating waste cooking oil into nyamplung biodiesel significantly reduces viscosity, density, and flashpoint while increasing the calorific value. Specifically, the addition of waste cooking oil altered the density from 912.74 kg/m³ in pure nyamplung biodiesel to 857.27 kg/m³, decreased the viscosity from 28.02 cStto 4.58 cSt, reduced the flash point from 223°C to 197°C, and increased the heating value from 7,626.59 cal/g to 8,348.94 cal/g.